2014
DOI: 10.1099/jmm.0.075465-0
|View full text |Cite
|
Sign up to set email alerts
|

Instant screening and verification of carbapenemase activity in Bacteroides fragilis in positive blood culture, using matrix-assisted laser desorption ionization–time of flight mass spectrometry

Abstract: Rapid identification of isolates in positive blood cultures are of great importance to secure correct treatment of septicaemic patients. As antimicrobial resistance is increasing, rapid detection of resistance is crucial. Carbapenem resistance in Bacteroides fragilis associated with cfiA-encoded class B metallo-beta-lactamase is emerging. In our study we spiked blood culture bottles with 26 B. fragilis strains with various cfiA-status and ertapenem MICs. By using main spectra specific for cfiA-positive and cfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…The mechanism of cfiA activation in these strains is unknown. A small number of isolates with similar characteristics has been previously described 14 33. Three strains with multiple cfiA gene copies have been previously reported, but correlation between copy number and the degree of resistance is unclear 7…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The mechanism of cfiA activation in these strains is unknown. A small number of isolates with similar characteristics has been previously described 14 33. Three strains with multiple cfiA gene copies have been previously reported, but correlation between copy number and the degree of resistance is unclear 7…”
Section: Discussionmentioning
confidence: 87%
“…Nonetheless, the approach has only been evaluated with bacterial collections containing a relatively small number of cfiA -positive isolates 10–12. Recent investigations have further shown that MALDI-TOF MS could be used to detect MBL activity mediated by cfiA in 3 hours 13 14. In addition, the performance of two commercial tests—double-ended Etest±EDTA (bioMerieux) and the KPC/MBL Confirm Kit—in detecting cfiA MBL in B. fragilis has also been evaluated 15.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, two different groups demonstrated that matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) was able to detect by-products resulting from the hydrolysis of a carbapenem in the presence of a bacterial extract of CPE (13,14). Since then, several investigators have improved the sensitivity of the method as well as the interpretation of the results (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…For the latter case, it is important to note that some variants show low enzymatic activity and hence require an extended incubation time (4 hr) to avoid false-negative results [ 49 50 ]. Further, the assay has been applied to samples obtained from positive blood culture, potentially avoiding a cultivation step using solid growth media [ 51 52 ]. Multiplexing, i.e., an assay with multiple antibiotics, may be feasible when lysates of bacteria are used [ 45 ].…”
Section: Astmentioning
confidence: 99%